Optimising Non-Thermal Acid Maturation of Giant Gourami (Osphronemus gouramy) as a Novel Food Processing Technology - Rendi Restiana Sukardi; Muhammad Rizal Hardiansyah M; Muhammad Nur Mannan; Meilinda Meilinda; Mohd Nizam Lani; Siti Supriyanti; Ade Yulianto (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to develop and optimise a technologically relevant non-thermal acid-induced maturation process for giant gourami by identifying effective citrus acid formulations and immersion durations that enable controlled myofibrillar protein denaturation for scientifically standardised and traditional Dekke Naniura processing. Methodology: A laboratory-based semi-controlled experimental design was applied using fresh gourami fillets immersed in organic acids derived from lime (Citrus aurantiifolia) and lemon (Citrus limon) juices at different ratios and immersion times. Maturation progression was evaluated using a semi-quantitative visual index (0–100%) supported by triplicate mean ± SD measurements. Observations included colour transformation, flesh firmness, and macroscopic protein denaturation, while microscopic assessment and mechanical texture analysis validated structural myofibrillar changes. Statistical analysis using one-way ANOVA and Tukey’s HSD determined significant treatment differences. Main Findings: The optimal condition was a formulation containing 75% lime juice and 25% lemon juice with an immersion duration of 1,140 minutes, achieving 96% maturation. This treatment produced homogeneous myofibrillar protein denaturation, uniform colour transformation, and increased flesh firmness under non-thermal conditions. Single-acid treatments showed slower and less uniform maturation, indicating a synergistic effect of mixed citrus acids. The dense muscle fibre structure and high myofibrillar protein content of gourami contributed to enhanced structural stability during maturation. Statistical analyses confirmed significant differences among treatments at most immersion times. Novelty/Originality of this study: This study proposes a reproducible and chemically optimised non-thermal maturation model integrating semi-quantitative, microscopic, and mechanical analyses, providing a scientifically validated framework for modern adaptation of traditional Batak naniura processing.